2012
DOI: 10.1590/s1519-69842012000400006
|View full text |Cite
|
Sign up to set email alerts
|

The southern Brazilian grassland biome: soil carbon stocks, fluxes of greenhouse gases and some options for mitigation

Abstract: The southern Brazilian grassland biome contains highly diverse natural ecosystems that have been used for centuries for grazing livestock and that also provide other important environmental services. Here we outline the main factors controlling ecosystem processes, review and discuss the available data on soil carbon stocks and greenhouse gases emissions from soils, and suggest opportunities for mitigation of climatic change. The research on carbon and greenhouse gases emissions in these ecosystems is recent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 31 publications
1
9
0
1
Order By: Relevance
“…The grassland matrix is dominated by C4 graminoid species, with the presence of forbs and some short shrubs (Marchiori, 2004; Overbeck et al, 2018). Highland grasslands form mosaics with isolated patches of Araucaria forest (Pillar, Tornquist, & Bayer, 2012). They shelter a high diversity of species, with many endemic species of flora and fauna (Bencke, 2009; Boldrini, 2009; Santos, Iop, & Alves, 2014), and are threatened by expanding crops and silviculture, with only 40% of the original grassland cover remaining (Vélez‐Martin et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The grassland matrix is dominated by C4 graminoid species, with the presence of forbs and some short shrubs (Marchiori, 2004; Overbeck et al, 2018). Highland grasslands form mosaics with isolated patches of Araucaria forest (Pillar, Tornquist, & Bayer, 2012). They shelter a high diversity of species, with many endemic species of flora and fauna (Bencke, 2009; Boldrini, 2009; Santos, Iop, & Alves, 2014), and are threatened by expanding crops and silviculture, with only 40% of the original grassland cover remaining (Vélez‐Martin et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…However, up to now, the focus of restoration ecology has been principally on forest vegetation or on the woody component of non-forest vegetation types such as Cerrado (Kageyama et al 2003b, Zamith & Scarano 2006, Durigan 2007, Sampaio et al 2007 These degradation processes not only lead to losses of biodiversity, but also reduce important ecosystem services provided by grasslands, such as carbon storage in soil, erosion control, water infiltration into the soil and forage production (White et al, 2000 andreferences therein, Tornquist &Bayer, 2009;Pillar et al, 2012). It is mostly unknown to which extent these functions or services can return to near-natural conditions under unassisted recovery, given that former grassland areas become available for such recovery following logging of pine or eucalypt plantations, or cessation of intensive arable use ( Figure 1).…”
Section: Programa De Pós-graduação Em Ecologia Universidade Federal mentioning
confidence: 99%
“…Triches et al (2015) suggested that the maintenance of grasslands could generally be attributed to the direct economic benefit that farmers and ranchers obtain from grazing these lands with beef and dairy cattle. In fact, the economic value of the grasslands has been indicated as being crucial for the conservation of these ecosystems (Pillar et al, 2012).…”
Section: Methodsmentioning
confidence: 99%